PENGEMBANGAN BAHAN AJAR MATERI POLA BILANGAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIK SMP - Ajas Juhara; Deti Ahmatika (UJMES (Uninus Journal of Mathematics Education and Science), 2022)
This research is motivated by the low ability of mathematical connections and the unavailability of teaching materials to improve students' mathematical connection skills. The purpose of this study was to develop mathematics teaching materials to improve students' mathematical connection skills with good characteristics and quality of teaching materials. This research uses qualitative and quantitative approaches. The method used is research and development (RD), with a modified Tessmer model design. The research subjects were class VIII students and a mathematics educator at a private junior high school located in Bandung district as well as a mathematics education lecturer. The instruments used were validation sheets, student questionnaires, educator questionnaires, observation sheets, and a set of mathematical connection tests. Data were collected through: validation of teaching materials, limited trials, and field trials. Based on data processing and analysis, two characteristics of the teaching materials developed consist of: material according to the 2013 curriculum; discovery learning model teaching materials design; evaluation according to mathematical connection ability indicators. The results of data analysis related to the quality of teaching materials show that the teaching materials developed are valid, practical, and effective. Thus it can be concluded that the developed teaching materials have characteristics to improve mathematical connection abilities and have valid, practical, and effective qualities.